Thermographic Behaviour of the Orbicularis Oris Muscle Under Different Provocative Tests. - Salles, Patrícia Vieira; Valentim, Amanda Freitas; Caldeira, Maria Luiza Neves; Haddad, Denise Sabbagh; Furlan, Renata Maria Moreira Moraes; Motta, Andréa Rodrigues (Journal of Oral Rehabilitation, 2026)
Background: Infrared thermography is an objective method for investigating muscle functioning, enabling inferences about physiology and therapeutics. This noninvasive and non‐ionising imaging diagnostic method allows real‐time visualisation of the vascular and musculoskeletal systems through skin microcirculation dynamics. It transforms information about the human body's thermal radiation, captured via infrared radiation, into an analysable image. Objective: To describe the thermographic behaviour of the orbicularis oris muscle during sustained contraction and chewing tasks. Methods: The study included 56 healthy women aged 18–52 years, who underwent thermographic evaluations before, during, and after performing sustained contraction and chewing tasks. The orbicularis oris muscle was analysed qualitatively and quantitatively using anatomical thermal areas and Student's t‐test to compare mean temperature data. Results: Qualitative analysis revealed temperature changes during the provocative tasks. A comparison of mean temperatures showed a significant temperature increase, corroborating the qualitative findings. The mean temperature variation per task was as follows: 0.57°C during lip compression, 0.20°C during lip protrusion, 0.57°C while chewing peanuts, 0.43°C while chewing crackers, and 0.37°C while chewing a bread roll. There was a decrease in mean temperature during the intervals between tasks, though insufficient to return to baseline levels, indicating a cumulative temperature effect between tasks. Conclusion: The orbicularis oris muscle temperature increased during the provocative tasks. The 2‐min interval between tasks was insufficient for the resting temperature to return to baseline levels. These findings confirm that thermography is an effective method for identifying such temperature changes.